2015
DOI: 10.5103/kjsb.2015.25.2.219
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of EMG According to Surface Type and Elastic Band Usage During the Pilates Superman Movement

Abstract: Objective : The purpose of this study was to analyze EMG according to surface type and elastic band usage during the pilates Superman movement. Method : The subjects were 10 female university students with a mean age of 27. The independent variables were surface type (yoga mat, air filled equipment, elastic mat) and elastic band usage. In order to measure muscle activity, the Noraxon(USA) was used. Eight muscles (upper trapezius, lower trapezius, thoracic spine, lumbar spine, gluteus maximus, gluteus medius, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Pilates Swimming prep performed in this study is the representative exercise of the core stabilization exercise [52] and is the exercise developing the back muscles of the whole body including the lumbar part and hips, and especially, this motion was reported to increase the muscle activity of the Gmed [26]. The Gmed and Gmax are important muscles for the pelvic stability, and weakened gluteus is closely related to back pain [53].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pilates Swimming prep performed in this study is the representative exercise of the core stabilization exercise [52] and is the exercise developing the back muscles of the whole body including the lumbar part and hips, and especially, this motion was reported to increase the muscle activity of the Gmed [26]. The Gmed and Gmax are important muscles for the pelvic stability, and weakened gluteus is closely related to back pain [53].…”
Section: Discussionmentioning
confidence: 99%
“…The study of muscle activity through EMG by Lee & Jeong [25] also reported that the muscle activity of RA muscle and EO muscle increased during Pilates Hundred motion. In addition, there is Swimming motion as lumbar extension exercise to strengthen the lumbar part among Pilates motions, and Swimming motion was reported to strengthen lumbar muscle strength and Gluteus muscle (GM) [26], and Lee & Jeong [25] also said that the muscle activity of LES muscle and GM increased during Beat motion and Brest stroke prep which are similar to Swimming motion. As shown above, Pilates Hundred motion and Swimming motion have been reported to be effective in the increase in abdominal (AB) muscle, LES muscle, and GM, but most of these studies studied the motions of Pilates for ordinary people without pain.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation